DISTEFANICERAS, A NEW NAME FOR THE GENUS DISTEFANIA FUCINI, 1931 (MOLLUSCA, CEPHALOPODA), PREOCCUPIED BY DISTEFANIA CHECCHIA-RISPOLI, 1917 (CRUSTACEA). TAXONOMIC IMPLICATIONS FOR SOME LATE PLIENSBACHIAN-EARLIEST TOARCIAN HILDOCERATIDAE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
Distefania, one of the several ammonites genera described during the thirties in the upper Pliensbachian faunas from Taormina (Sicily), is involved by a case of homonymy. A recent study on the ammonoid assemblages of the late Pliensbachian-early Toarcian transition in the Apennines evidenced that it would be useful to keep a separate and valid name for this previously underrated Mediterranean genus, in order to better understand the time intervals and improve correlations. Moreover, it shows morphologic and sutural differences compared to the genera with which it is usually mistaken, and its vertical range is partially different as well. Therefore, in accordance with the ICZN rules, the form in question is here renamed as Distefaniceras.
Keywords: Ammonites; Taxonomy; Mediterranean Tethys; Early Jurassic